Cytology and associated histology of biliary and pancreatic duct striutures: how good is our correlation? - Coetzee, Kirstin Janine (My University, 2015)
Endoscopic Retrograde Cholangiopancreatography (ERCP) with bile and pancreatic duct brushings is a first-line diagnostic investigation in patients with pancreatic carcinoma and cholangiocarcinoma presenting with obstructive jaundice. Biliary brushing cytology has a high specificity approaching 100%, but sensitivity is only modest, with reported ranges in the literature of 42-88%.